Sobre el texto: "PRÁCTICAS FÍSICODEPORTIVAS. ACTITUDES Y TENDENCIAS DE ESCOLARES COLOMBIANOS". - Bustos Viviescas, Brian Johan; García Yerena, Carlos Enrique; García Galviz, John Alexander (Atenas, 2024)
Sobre el texto: "PRÁCTICAS FÍSICODEPORTIVAS. ACTITUDES Y TENDENCIAS DE ESCOLARES COLOMBIANOS".